1970
DOI: 10.1111/j.1365-2184.1970.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Renewal of Goblet and Paneth Cells in the Small Intestine

Abstract: Single and repeated injections of 3H‐thymidine were used to demonstrate that both Paneth and goblet cells in the small intestine of the rat undergo renewal but do not themselves proliferate. Goblet cells are renewed much faster than Paneth cells and probably migrate with the columnar cells from the crypts to the villi. Attempts were made to identify the proliferative precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…The exact point during cell maturation at which the Paneth cells appear is also unknown, as is whether their progenitors move immediately downwards (Hampton 1968), or initially move upwards with the general cell flow and then move down to the crypt base. However, the fully differentiated Paneth cells appear after 3 days (Cairnie 1970) and, unlike the other upwardly moving cell types, have a much longer lifetime within the animal, lasting for over two weeks (when they appear to be removed by phagocytosis, Troughton & Trier 1969;Cheng & Leblond 1974a). The intercalated cells (non-Paneth cells located near the crypt base) may be early Paneth cells (Hampton 1968), although some have argued these are actually stem cells (Bjerknes & Cheng 1981).…”
Section: Differentiated Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact point during cell maturation at which the Paneth cells appear is also unknown, as is whether their progenitors move immediately downwards (Hampton 1968), or initially move upwards with the general cell flow and then move down to the crypt base. However, the fully differentiated Paneth cells appear after 3 days (Cairnie 1970) and, unlike the other upwardly moving cell types, have a much longer lifetime within the animal, lasting for over two weeks (when they appear to be removed by phagocytosis, Troughton & Trier 1969;Cheng & Leblond 1974a). The intercalated cells (non-Paneth cells located near the crypt base) may be early Paneth cells (Hampton 1968), although some have argued these are actually stem cells (Bjerknes & Cheng 1981).…”
Section: Differentiated Phenotypesmentioning
confidence: 99%
“…The usefulness of this type of stem cell functional assay was first described by Till & McCulloch in 1961 as a spleen colony assay for haemopoietic stem cells. The philosophy was then adapted to the gut as a macro (late times) and then micro (early times) colony assay (Withers & Elkind 1969, 1970Potten & Hendry 1985). This either measures the gross morphological regeneration of the denuded gut following high dose irradiation (macro) or the regeneration of individual crypts (micro).…”
Section: Clonogenic Cell Estimates From In Vivo Regeneration Modelsmentioning
confidence: 99%
“…To date, it has been shown that the Paneth cell has no self-replicating ability (THROUGHTON and TRIER, 1969;CHENG et al, 1969, CAIRNIE, 1970CHENG, 1974b), and seems to be derived from crypt-base columnar cells and degenerate in situ (CHENG at al., 1969;CHENG, 1974b). The turnover time of the population is thought to be much longer than that of goblet cells (CHENG et al, 1969;CAIRNIE, 1970;CHENG, 1974 a, b). …”
Section: The Paneth Cellmentioning
confidence: 99%
“…Although a few goblet cells are capable of mitosis (CAIRNIE, 1970;SHIMAMOTO, 1970), a majority is produced from generative cells in crypts. Labelled goblet cells appear in the villus 20-24 hrs later than labelled columnar cells after 3H-thymidine administration (MERZEL and LEBLOND, 1969;CAIRNIE, 1970). Both cells, however, migrate along the villi at the same speed.…”
mentioning
confidence: 99%
“…However, it cannot be excluded that the mucous cells may also derive from proliferating crypt-base columnar cells (14). The decision to study goblet cell behaviour was also made in order to examine the cellular differentiation process in the small intestine after irradiation.…”
mentioning
confidence: 99%